PENERAPAN METODE PEMBELAJARAN LANGSUNG TERHADAP TEKNIK DASAR PASSING BAWAH DALAM PERMAINAN BOLA VOLI - Indri Susilawati; Muhammad Satria Mulyajaya (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2022)
TheApplication of DirectInstruction Method on underhand Passing Basic Techniques in Volleyball toward the VIIth Grade Students of SMPN 20 Mataram”. The purpose of this research was to improve underhand Passing Basic Techniques in Volleyball toward VIII Grade Students of SMPN 20 Mataram through direct instruction method. This is a classroom action research (CAR). The study was conducted in two cycles, each cycle consisting of planning, implementation, observation, and reflection. The subjects research is 26 Students of VIII Grade SMPN 20 Mataram. Instruments used in this research were lesson plan, observation sheet toward students’ activity and students’ worksheet. The results of this research was obtained based on the assessment of three aspects that are psychomotor, affective, and cognitive. The result of assessment showed that learning achievement data obtained in cycle I Learning outcomes of underhand passing in volleyball obtained 8 students or completeness percentage of 30.77%. While on the second cycle increased 21 students or the percentage of completeness be 80.77% of the total number of students. So the increase from the first cycle to the second cycle were 50% or 13 students. Based on the data analysis, it could be concluded that the application of direct instruction method can improve underhand passing basic techniques in volleyball toward the VIIth Grade Students of SMPN 20 Mataram 2021/2022.